2013
DOI: 10.1089/acm.2011.0868
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Holistic Yoga Program on Endocrine Parameters in Adolescents with Polycystic Ovarian Syndrome: A Randomized Controlled Trial

Abstract: A holistic yoga program for 12 weeks is significantly better than physical exercise in reducing AMH, LH, and testosterone, mFG score for hirsutism, and improving menstrual frequency with nonsignificant changes in body weight, FSH, and prolactin in adolescent PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 31 publications
1
38
0
Order By: Relevance
“…Through the methods of body posture, breathing training, and consciousness meditation, overall well-being could be improved with positive benefits to the nervous system [38], endocrine system [39], cardiovascular system [40], respiratory system [41], and immunity [42]. Few studies have demonstrated the effects of mindfulness and yoga on well-being, somatic effects of stress, immune system and physical symptoms and chronic conditions [43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…Through the methods of body posture, breathing training, and consciousness meditation, overall well-being could be improved with positive benefits to the nervous system [38], endocrine system [39], cardiovascular system [40], respiratory system [41], and immunity [42]. Few studies have demonstrated the effects of mindfulness and yoga on well-being, somatic effects of stress, immune system and physical symptoms and chronic conditions [43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Even though one study reported changes in E 2 levels, it was conducted without scientific rigor. Yoga and meditation practices have been correlated with certain hormone variations.…”
Section: Discussionmentioning
confidence: 99%
“…Measures of hormone and immune function have also been explored especially as an adjunct measure to various clinical outcomes (O’Halloran et al, 1985; Walton et al, 1995; Tooley et al, 2000; Infante et al, 2001). Hormonal changes associated with spiritual practices include those to cortisol, noradrenaline, endorphins, sex hormones, and growth hormone (Werner et al, 1986; MacLean et al, 1997; Nidhi et al, 2013; Sooksawat et al, 2013). Again though, these practices were not specifically spiritual.…”
Section: Objective Measures Of Spiritualitymentioning
confidence: 99%